The Dramas of Manojlo Đorđević Prizrenac on the Serbian Stage - Pejčić, Aleksandar S. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The paper interprets and evaluates the dramas performed by Manojlo Đorđević Prizrenac: Slobodarka, Zlatna grivna, and Jasmina and Irena. The first part of the paper focuses on the key poetic, dramaturgical, and genre features of these dramas, demonstrating that Prizrenac was a good playwright who mastered this demanding form very early on. The dominant meaning layers of each drama were interpreted separately (action, plot, space, and conception of characters) from a structural, semiological, and cultural point of view. The final part of the paper examines the reception of criticism as well as the place of Prizrenac’s drama opus in the history of Serbian theater from a literary-historical and theatrical perspective. His dramas were performed with nice scenic success in the National Theaters in Belgrade and Novi Sad, as well as Nikšić and Niš.
Keywords: Manojlo Đorđević Prizrenac; tragedy; melodrama; civic drama; genre; theatricalization; theater